THE EFFECT OF COFFEE TYPE, PRICE AND SERVICE ON CUSTOMER SATISFACTION AT COFFEE SHOPP RESTU BUNDA, MEDAN CITY - Sri Wahyuni Br Maha; Deni Faisal Mirza; Jontrapolta Sembiring; Rosdiana Gultom (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study aims to analyze the effect of coffee types, pricing, and service on customer satisfaction at RESTU BUNDA Coffee Shop in Medan City. The research is motivated by the high demand for coffee products, affordable prices suitable for students, and friendly, responsive service offered by the coffee shop. This research uses a quantitative approach with an associative causal method. The sample consisted of 91 respondents who were customers of RESTU BUNDA Coffee Shop. Data were collected through observation, questionnaires, and documentation. Data analysis includes validity tests, reliability tests, classical assumption tests, and hypothesis testing using t-tests and F-tests. The results show that coffee type, pricing, and service have a positive and significant effect on customer satisfaction, both partially and simultaneously. These findings imply that RESTU BUNDA Coffee Shop should maintain the quality of its coffee, offer competitive prices, and enhance service quality to sustain and increase customer satisfaction.